Answer :

Given:

1st A.P. series: 63, 65, 67 …


2nd A.P. series: 3, 10, 17


Therefore, the nth term of the first series tn1 must be equal to nth term of the second series tn2


tn1 = a1 + (n-1)d1


tn2 = a2 + (n-1)d2


where


a1 & a2 are the first terms of the 1st and 2nd A.P. Series respectively


d1 & d2 are Common differences of the 1st and 2nd A.P. Series respectively


According to the problem:


tn1 = tn2


a1 + (n-1)d1 = a2 + (n-1)d2


Putting the values, we get


63 + (n-1) × 2 = 3 + (n-1) × 7


60 = 5(n-1)


12 = n-1


Answer: The Value of n = 13

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Glimpses of IndiaGlimpses of IndiaGlimpses of India39 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses